P-O01 A patient education video to support the management of post-gastrectomy / oesophagectomy syndromes. (16th December 2021) - Roberts, Geoffrey; Stone, Andrew; Sunderland, Nicola; Grimes, Sam; Reimann, Frank; Gribble, Fiona; Hardwick, Richard
Abstract: Background: Oesophagectomy and gastrectomy result in profound and life-long changes in eating behaviour and appetite, and significant post-prandial symptoms. Despite decades of research, and recent advantages in the understanding of gut physiology, medical approaches to post-resectional patient care remain limited. The mainstay of treatment is patient education. Using clinical and lab-based studies, we investigated the effects of altered gut hormone secretion in patients after surgery for oesophageal and gastric cancer. We then produced a partially animated patient information video to better equip our patients to manage their altered alimentation. Methods: The scientific background to the video was previously presented at AUGIS, and published. Studies included examination of eating behaviour, post-prandial symptoms, glucose homeostasis, gut hormone profiles and intestinal transcriptomic / peptidomic changes in a cohort of patients after oesophagectomy and gastrectomy. The movie storyboard and script were written by a team of surgeons, dietitians, patient representatives, clinical scientists and communications specialists. The goal was to communicate the physiological basis of altered eating in post-operative patients and appropriate nutritional strategies. Results: The video is now freely available on Vimeo at: https://vimeo.com/356892336 It is in routine use for pre- and post-operative patient education. Conclusions: Multimedia patient education is a useful tool to help manage the late effects of upper GI cancer treatment.